HUBUNGAN FERITIN SERUM DENGAN KADAR IL-2 PADA PENDERITA ANEMIA DEFISIENSI BESI - Losen Adnyan, I Wayan; Bakta, I Made; Suega, Ketut; Darmayuda, Tjok Gde (journal of internal medicine; Vol. 8, No. 1 Januari 2007)
Iron deficiency anemia is one of the most common single nutrient deficiency in the world, impairs lymphocyte proliferation in humans and laboratory animals. The mechanisms are not fully understood. Cellular iron availability modulates the differentiation and proliferation of Th-1 and Th-2 subsets. Th-1 clones are very sensitive to treatment with antitransferrin receptor antibodies, resulting in inhibition of their DNA synthesis. Th-1-mediated immune effector function may be much more sensitive to changes in iron homeostasis in vivo. Th-1 produce IFN- and IL-2. The effects of iron deficiency on immunity remain controversial. Cross sectional study was performed to determine the relationship between iron status (serum ferritin) and IL-2 production in patients with iron deficiency anemia. This relationship was assessed in 33 adult patients. Infection, malnutrition, malignancy, acute bleeding and using immunosuppressive medicines were excluded. Iron deficiency anemia was defined by Kerlin et al criteria. Serum ferritin was measured by immunometric assay and IL-2 was measured by immunoassay solid phase ELISA. The mean of Hb was 6.27 ± 2.19 g/dL, serum ferritin 30.07 ± 49.41, IL-2 2.26 ± 1.30. The most causes of this anemia were chronic bleeding i.e. peptic ulcer, ancylostomiasis, menorrhagia, hemorrhoid and hematuria. There was not correlation between serum ferritin and IL-2 (r = 0.118; p = 0.512). There was not correlation between Hb and IL-2 too (r = 0.220; p = 0.219). Lack of the correlation may be caused by some conditions i.e. without activated T cell, inadequately controlled the other trace elements or co-morbid diseases. Our data support that there is not correlation between serum ferritin, Hb and IL-2 production by lymphocyte without stimulation. Further prospective studies are needed to determine relationship between iron status and immune function.
Keywords: iron deficiency anemia, serum ferritin, Hb, IL-2